The Influence of Tafsir Medium on the Interpretive Process: A Case Study of Tafsir al-Qur’an Aktual on Bangsaonline.com - Maulana, Moch Dimas; Samaila, Ali (Digital Muslim Review, 2024)
Technological advances have transformed the presentation of tafsir (Qur’an commentary) across various media, from oral traditions to manuscripts, printed books, and now digital platforms. This study explores whether these platforms merely serve as vessels or actively influence a mufassir’s (Qur’an interpreter’s) approach. Focusing on Tafsir al-Qur’an Aktual, published on Bangsaonline.com, it examines how the medium affects interpretative processes. Written by Ahmad Musta’in Syafi’i, a prominent pesantren leader in East Java, this tafsir has appeared in Harian Bangsa newspaper since March 2000, marking the first Indonesian tahlīli tafsir in a newspaper. Employing Howard Giles’ Communication Accommodation Theory, the study reveals that the newspaper medium shaped Musta’in’s interpretations to accommodate lay readers. This influence is reflected in his language style, word choice, and the inclusion of Javanese terms. He also links verses to everyday events to ensure relevance for his audience. However, the study identifies instances of “overaccommodation,” where Musta’in connects verses to contemporary sociopolitical issues, occasionally deviating from their original meanings. This phenomenon, termed “obsessiveactualization,” underscores the media’s role in shaping a mufassir’s interpretative process.